Influence of Financial Literacy and Financial Inclusion on Millennials’ Investment Decisions in North Luwu Capital Market - Andini, Faula; jasman, jumawan; Dewintari, Putri (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study aims to examine the influence of financial literacy and financial inclusion on millennials’ investment decisions in the North Luwu capital market. Methodology: A quantitative approach was applied using a structured questionnaire distributed to 83 respondents selected through Slovin’s formula. The data were analyzed using multiple linear regression via SPSS software. Results: Both financial literacy (β = 0.471, p < .001) and financial inclusion (β = 0.256, p < .001) significantly and positively influence millennials’ investment decisions. The adjusted R² value of 0.646 indicates that 64.6% of the variance in investment decisions is explained by the two predictors. Findings: Financial literacy has a more dominant effect than financial inclusion, emphasizing the importance of financial understanding in making rational investment decisions. Novelty: This study addresses a geographic gap by focusing on millennials in a semi-peripheral region (North Luwu), where empirical data on investment behavior are still scarce. Originality: The study offers an integrative framework by employing the Theory of Planned Behavior (TPB) to connect financial literacy and inclusion with investment decision-making, a combination rarely explored in previous literature. Conclusion: Improving both financial literacy and financial inclusion concurrently is essential to fostering smarter, more inclusive investment behaviors among millennials, particularly in underrepresented regions. Type of Paper: Empirical Research Paper.